Climate-induced salinization may lead to increased lake nitrogen retention. (1st January 2023) - Jiang, Xingyu; Liu, Changqing; Hu, Yang; Shao, Keqiang; Tang, Xiangming; Zhang, Lu; Gao, Guang; Qin, Boqiang
Highlights: Increased salinity inhibited denitrification rates in inland lakes. Nitrogen retention capacity is relatively stronger in saline than freshwater lakes. Climate change is expected to alter lake N fate via changing in salinity. Abstract: Salinization caused by climate change and nitrogen (N) pollution are both important environmental threats for inland lakes. However, evaluating their interactive effects continues to be challenging. Here, field observation and microcosmic experiments were conducted in six lakes of East Asia with the different salinity and climate characteristics, to explore the response of the key N cycle processes related to N fate to the climate-induced change in salinity. The results indicated that increased salinity inhibited denitrification, which was the outcome of two cumulative effects: the long-term microbial adaptation effect and the direct salinity stress. Whereas increased salinity had unsignificant or positive effects on dissimilatory nitrate reduction to ammonium. It had caused that N retention capacity is relatively stronger in saline than freshwater lakes. Inland lakes are long-term basin-wide integrators of climatic conditions that drying (salinization) and wetting (desalination) with climate change. In semi-arid regions of East Asia, lake shrinkage, salinization and increasing temperature driven by climate warming and drying may exert a negative impact on N pollution through concentrating, decreasing denitrification and increasing ammonium release from sediment. The threat of climate change on these lakes is not just the quantity of water, but its quality. Graphical abstract: Image, graphical abstract